Gaps of Medication Treatment Management Between Guidelines and Real-World for Inpatients With Type 2 Diabetes in China From Pharmacist’s Perspective - Song, Zhi-Hui; Wang, Xing-Long; Wang, Xiao-Feng; Liu, Jing; Luo, Sang-Quzhen; Xu, Shan-Shan; Cheng, Xiao; Bai, Jie; Dong, Li-ming; Zhang, Chao; Zhou, Jian-Bo (Frontiers in Endocrinology, 2022)
Background: The prevalence of diabetes mellitus remains high in China, and more cardiovascular and cerebrovascular adverse events due to diabetes mellitus are likely to occur in the future. Objective: To analyze the gap between the current pharmacotherapy management and the guidelines for inpatients with type 2 diabetes mellitus from the perspective of pharmacists so as, to provide a reference for optimal pharmacotherapy management methods and models for patients with type 2 diabetes mellitus. Methods: The study was a cross-sectional observational study. The study was conducted by investigating and analyzing the use of glucose-lowering drugs, adjustment of blood pressure management strategy, lipid management, weight management, and application of antiplatelet drugs in type 2 diabetes inpatients. Results: A total of 1086 patients with type 2 diabetes were included. Metformin, glycosidase inhibitors, and basal insulin were the most used among type 2 diabetes inpatients. The use of SGLT-2, GLP-1 RAs, DPP-4, and metformin all showed significant increase. SGLT-2 inhibitors (SGLT-2i) showed the fastest increase from 2020 to 2021 (14.5% vs. 39.6%); hHowever, the application rate of SGLT-2i was low among patients with combined ASCVD, renal insufficiency, and diabetic nephropathy (46.4%, 40.9%, and 45.8% respectively). For patients with substandard blood pressure at admission, the average rate of intervention by endocrinologists for adjusting the antihypertensive regimen during hospitalization was 55.6%, and the application rate of ACEI/ARB drugs reached 64.4%. The application rate of statins among patients with type 2 diabetes was still relatively high, at 78.8%. However, the overall intervention rate for patients with suboptimal LDL-c was only 24.1%. The application rate of antiplatelet agents for patients with ASCVD was 77.6%, which was higher than that for patients without ASCVD. Conclusion: There is still a gap between the practice of medicine therapeutic management of Chinese inpatients with type 2 diabetes and the guidelines, especially in the application of GLP-1RAs and SGLT-2i in patients with concomitant ASCVD, diabetic nephropathy, and renal insufficiency. Meanwhile, physicians and pharmacists should pay more attention on achieving blood pressure and LDL-c standards in type 2 diabetic patients and provide timely interventions.